1989
DOI: 10.1002/1097-0142(19891201)64:11<2199::aid-cncr2820641102>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic implications of internuclear bridging in myelodysplastic syndrome. An eastern cooperative oncology group/southwest oncology group cooperative study

Abstract: Numerous morphologic features have been described in bone marrow and peripheral blood in myelodys-plastic syndrome (MDS). We draw attention to a high incidence of a subtle morphologic feature, internuclear bridging (INB), not previously recognized as a morphologic feature in MDS. The occurrence of INB in MDS suggests an underlying abnormality of mitotic division that could explain the impaired production of hematopoietic cells, the addition and deletion cytogenetic changes, and the stepwise disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It must be emphasized that by LM we did not find INB in 21% of our patients with molecular proven CDAI, although they are considered as the most specific LM morphological hallmark of the disease . However, their specificity has been questioned as they also may appear as an unspecified dyserythropoietic finding in acute myeloid leukemia, in myelodysplastic syndrome before leukemic transformation, in megaloblastic anemia, and in the presence of unstable hemoglobin . Although we did not count the morphological LM findings found in each sample, Heimpel et al found those to be infrequent, for example, INB found in 3% of erythroblasts (range 1.4‐7.9) …”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized that by LM we did not find INB in 21% of our patients with molecular proven CDAI, although they are considered as the most specific LM morphological hallmark of the disease . However, their specificity has been questioned as they also may appear as an unspecified dyserythropoietic finding in acute myeloid leukemia, in myelodysplastic syndrome before leukemic transformation, in megaloblastic anemia, and in the presence of unstable hemoglobin . Although we did not count the morphological LM findings found in each sample, Heimpel et al found those to be infrequent, for example, INB found in 3% of erythroblasts (range 1.4‐7.9) …”
Section: Discussionmentioning
confidence: 99%
“…In addition to chromosomal instability noted by many FA investigators, we have noted internuclear bridging peculiar to FA mutant cells. Internuclear bridging is a phenomenon seen in cells displaying genomic instability (51,52). Cells with abnormal chromosomal segregation and chromosomal structures such as those in FA can form internuclear bridging, presumably because of lagging chromosomes (53).…”
Section: Fig 2 Fancg Is Phosphorylated In Vivomentioning
confidence: 99%
“…Furthermore, although internuclear chromatin bridges which connect partially separated erythroblasts are characteristic of CDA type I, they are also encountered in acquired dyserythropoiesis, for example in some patients with the acquired myelodysplastic syndrome (Bethlenfalvay et al, 1986;Head et al, 1989).…”
Section: General Characteristics Of Congenital Dyserythropoietic Anaementioning
confidence: 99%